2021
DOI: 10.1186/s40659-021-00350-6
|View full text |Cite
|
Sign up to set email alerts
|

Demethylzeylasteral (T-96) initiates extrinsic apoptosis against prostate cancer cells by inducing ROS-mediated ER stress and suppressing autophagic flux

Abstract: Background Demethylzeylasteral (T-96) is a pharmacologically active triterpenoid monomer extracted from Tripterygium wilfordii Hook F (TWHF) that has been reported to exhibit anti-neoplastic effects against several types of cancer cells. However, the potential anti-tumour effects of T-96 against human Prostate cancer (CaP) cells and the possible underlying mechanisms have not been well studied. Results In the current study, T-96 exerted significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 66 publications
(74 reference statements)
1
1
0
Order By: Relevance
“…What's more, it is well-known that excess release of ROS causes ER stress (Celesia et al, 2020). Under oxidative stress conditions, ER stress plays a vital role in the induction of apoptosis and autophagy in various tumors including osteosarcoma (Wang et al, 2019), melanoma (Liu, Kang, et al, 2019), prostate cancer (Yang et al, 2021). Our current results demonstrated that GNA induced ER stress by upregulating the expression levels of p-IRE1, Bip, and CHOP in PCa cells.…”
Section: Discussionsupporting
confidence: 58%
“…What's more, it is well-known that excess release of ROS causes ER stress (Celesia et al, 2020). Under oxidative stress conditions, ER stress plays a vital role in the induction of apoptosis and autophagy in various tumors including osteosarcoma (Wang et al, 2019), melanoma (Liu, Kang, et al, 2019), prostate cancer (Yang et al, 2021). Our current results demonstrated that GNA induced ER stress by upregulating the expression levels of p-IRE1, Bip, and CHOP in PCa cells.…”
Section: Discussionsupporting
confidence: 58%
“… 69 Apart from the compounds mentioned above, other small-molecule compounds that induce apoptosis by targeting TNFR-related proteins are also summarized in Table 1 . 70 77 …”
Section: Crucial Signaling Pathways Of Rcd Subroutines In Cancermentioning
confidence: 99%